2022
DOI: 10.1159/000525477
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Pain Assessment Practices for Cognitively Intact and Impaired Older Adults in Intensive Care Units

Abstract: <b><i>Introduction:</i></b> Pain is still under-recognized and undertreated among intensive care unit (ICU) patients, such as those being intubated or with dementia, cognitive impairments, or communication deficits due to inability to self-report. This study aimed to describe nurses’ pain assessment practices for cognitively intact and impaired older adult ICU patients. <b><i>Methods:</i></b> A descriptive correlational study of a convenience sample of 200 regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…Our study found that most nurses who used pain assessment tools worked in private hospitals. Our findings were supported by the finding of a recent study [9] that private-hospital and recently graduated nurses are more skilled in pain assessment methods than senior nurses working in public hospitals.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study found that most nurses who used pain assessment tools worked in private hospitals. Our findings were supported by the finding of a recent study [9] that private-hospital and recently graduated nurses are more skilled in pain assessment methods than senior nurses working in public hospitals.…”
Section: Discussionsupporting
confidence: 88%
“…Pain is still undertreated among ICU patients, especially cognitively impaired patients [9]. Given that pain is a significant problem among critically ill adult patients, nurses play a crucial role in its management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can hinder individuals' mobility and ability to perform daily activities [1,3]. Despite considering pain management a patient's fundamental right during their hospital stay, they still experience it [4,5]. Pain management is nurses' moral responsibility as they contact patients more than any other healthcare provider [6].…”
Section: Introductionmentioning
confidence: 99%